Optimization of dynamic parameters of straddle monorail vehicle to improve pantograph-catenary contact quality - ZHANG Yuejun; YANG Zhen; DU Zixue; WEN Xiaoxia; XU Zhouzhou (机车电传动)
Because straddle monorail vehicles run on rubber wheels, the contact status between the pantograph and the catenary is hard to control, and the abrasion on the current-receiving sliding block on the pantograph is serious. In order to reduce the abrasion on the sliding block, a sensitivity analysis method was used in this paper to analyze the influence degree of vehicle dynamics parameters on the coupling force of pantograph and catenary based on the dynamic simulation analysis model of "vehicle-pantograph-catenary" system. The average value of the pantograph-catenary contact force was considered as the optimization objective, and dynamics parameters of the vehicle were optimized by non-dominated sorting genetic algorithm (NSGA-II). The results show that the rigidness of the running tires and the guide tires has a great influence on the pantograph-catenary contact quality , and the standard deviation of the contact force decreases to a certain degree at different speed after parameter optimization. The abrasion problem of pantograph sliding block of straddle monorail vehicle can be improved by optimizing the radial rigidness of tires.